Book Review: Praveen Jha and Geetha Rani (eds), Right to Education in India: Resources, Institutions and Public Policy. Issue 3 (December 2016) - Venkataraman, L. N.
Praveen Jha and Geetha Rani (eds), Right to Education in India: Resources, Institutions and Public Policy . New Delhi: Routledge, 2016, ₹895 (hardback), 366 pp.